2008
DOI: 10.1177/183335830803700103
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Factors Affecting the Quality of Hospital Clinical Coding

Abstract: The influence of organisational factors on the quality of hospital coding using the International Statistical Classification of Diseases and Health Related Problems, 10th Revision, Australian Modification (ICD-10-AM) was investigated using a mixed quantitative-qualitative approach. The organisational variables studied were: hospital specialty; geographical locality; structural characteristics of the coding unit; education, training and resource supports for Clinical Coders; and quality control mechanisms. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 10 publications
(9 reference statements)
3
66
1
Order By: Relevance
“…Healthcare organisations need to continue to assess clinical documentation and identify problems, 35 as well as adopt site-specific strategies known to improve coding quality, such as: improved coder career opportunities; higher staffing levels; reduced throughput; and increased coder interactions with clinical staff. 36 A study in 2002 demonstrated that when trauma nurse case managers who routinely collected trauma data and coordinated patient care collaborated with clinical coding staff, coding accuracy and financial return for the hospital were improved. 10 More recently in NSW, the Health Education and Training Institute has implemented a Clinical Coding Workforce Enhancement project and will be more closely involved in the recruitment, education and training of clinical coders.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare organisations need to continue to assess clinical documentation and identify problems, 35 as well as adopt site-specific strategies known to improve coding quality, such as: improved coder career opportunities; higher staffing levels; reduced throughput; and increased coder interactions with clinical staff. 36 A study in 2002 demonstrated that when trauma nurse case managers who routinely collected trauma data and coordinated patient care collaborated with clinical coding staff, coding accuracy and financial return for the hospital were improved. 10 More recently in NSW, the Health Education and Training Institute has implemented a Clinical Coding Workforce Enhancement project and will be more closely involved in the recruitment, education and training of clinical coders.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] However, coders constitute only part of the equation in coding quality; their output depends on the quality of the input, which is physician documentation of a patient's course in hospital. As physician researchers, we acknowledge that many of the identified physician-related barriers are structural and systemic, extending beyond the control of physicians alone.…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8][9][10] Most studies on barriers to coding that result in highquality administrative data have focused on coder-related barriers concerning their training, knowledge and evaluation standards. [11][12][13][14][15][16][17] One barrier that is consistently described by coders is the lack of precise documentation in clinical charts, 1,13,18 which accounts for half of the disagreements in diagnostic codes among coders. 10 Although physicians provide the main sources of chart documentation, the role that they play in determining the quality of coded data remains unknown.…”
mentioning
confidence: 99%
“…The two lead articles (Alem et al 2008;Santos et al 2008) in this issue of HIMJ highlight the need to take into account the environment of work when examining information exchange in a clinical setting and the quality of hospital based coding. These two research articles are followed by a Professional Practice and Innovation section, which provides insights into a variety of current initiatives related to the management of health information.…”
Section: Joanne Callenmentioning
confidence: 99%
“…The two peer-reviewed articles in this issue (Alem et al 2008;Santos et al 2008) examine the environment of work, one clinical and the other a clinical coding unit, and both use quantitative and qualitative methods in their design. Alem and her colleagues (2008) report on medical handovers, and how information exchange in this complex work process takes place.…”
Section: Joanne Callenmentioning
confidence: 99%